Conceptual design of universal wireless navigation system in public amenities (internal facility) for physically blind people (disabled) / Thamil Selvam Kanniah - Thamil Selvam, Kanniah (2018)
There are many people want to live with happiness without obstacles and burden due to physical disabilities. Since earlier the accumulation of the number of physical vision loss has been increasing around 2 million in Malaysia. Majority of them did not take care of their vision when their eye sight started to decrease. This has affected their vision as it started to become dim daily. This has obtained an eminent of interest of the researcher on an assistive technology research for public amenities in this country. It has been proven in various studies, that there is a correlation between a numbers of navigating autonomous mobility assistant for physically blinded. Therefore, this study aimed to construct a conceptual design together with cost-effective prototype design for disabled. The new product introduce of a universal wireless navigation system device with an equipped voice synthesis raspberry device to improve the quality of life for physically blinded and visually impaired. This design integrated with hardware and software tools to help the physically blinded and special group together for those who have lost their vision along their life journey due to an undesirable event. Therefore, researcher decided to develop a Universal wireless navigation system by taking into consideration the safety factors, ergonomics and accuracy of information to be provided for the physically blind people to accomplish their daily routines without any personal assistance. It will take around 2 seconds only for the participants to detect their desired location through the designated device. At the same time, participants able to obtain latest multiple features which can be used be all over Malaysia and even world. The physically blind will be obtained benefit once the government of Malaysia approved including, Ministry of welfare and World Blind Organization approval to sell in the market.